Use of Transnasal Humidified Rapid-Insufflation Ventilatory Exchange for Emergent Surgical Tracheostomy: A Case Report. Issue 9 (1st November 2017) - Desai, Neel; Fowler, Anna
Abstract : Transnasal humidified rapid-insufflation ventilatory exchange (THRIVE) is a novel airway technique that utilizes high-flow humidified nasal oxygen. It can extend apnea time and maintain oxygen saturation. Here we report the use of THRIVE in a 35-year-old man who required emergent surgical tracheostomy for a clinically relevant compromised airway secondary to acute supraglottic and glottic pathology. Intravenous sedation resulted in hypoventilation close to apnea. THRIVE maintained oxygen saturation for 40 minutes until transient desaturation developed after complete airway obstruction.